Thomas Lickona's Idea on Character Education Which Builds Multicultural Awareness: Its Relevance for School/Madrasah in Indonesia - Kurniawan, Syamsul; Fitriyani, Feny Nida (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2023)
This paper departs from the background of library research. The purpose of this article is to reveal how Thomas Lickona's idea of character education builds multicultural awareness, and how relevant it is to education in school/madrasah in Indonesia. The primary data source is a book written by Thomas Lickona entitled Educating for Character, which the author using the content analysis method used to analyze Lickona's ideas. Based on the analysis of this book, Lickona's idea of character education that builds multicultural awareness is relevant to be applied, namely a comprehensive model, which is implemented with due regard to: first, a positive culture, which is created by developing an overall madrasah environment that supports and strengthens the values that are taught by educators in the classroom; second, the importance of models with positive attitudes and behavior from the leaders of educational institutions, educators, educational staff, and other elements as models for students to behave positively; and third, involving parents or guardians of each student, as well as the community and other components outside the school/madrasah as work partners to support student learning in values or character.